Not All Borders Are Global: Exploring Teacher-Librarian Collaboration in Math and Science - Latham, Don; Gross, Melissa; Julien, Heidi; Witte, Shelbie (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2016)
This poster reports the results of four focus groups held with high school math and science teachers and school and public librarians to explore how teachers and librarians can collaborate most effectively to help students develop 21st Century Skills in order to prepare them for STEM-related jobs. Cette affiche présente les résultats de quatre groupes de discussion entre des enseignants en mathématiques et en sciences au lycée et des bibliothécaires de lycée ou de bibliothèque publique, cherchant à explorer la façon dont les enseignants et les bibliothécaires peuvent collaborer plus efficacement pour aider les élèves à développer des compétences du 21e siècle afin de les préparer à des emplois en sciences, technologie, ingénierie et mathématiques (STIM).